Profil Kondisi Fisik Atlet Futsal Satria Mandiri Kota Pasuruan - Rayes Maulana H.W; Moch Yunus; Yulingga Nanda Hanief (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the profile of the physical condition of Satria Mandiri futsal athlete Pasuruan City. This research is a quantitative descriptive research. The subjects of this study were 30 Satria Mandiri futsal players in Pasuruan City. In this study, sampling used total sampling techniques. The data collection process was carried out using 4 instruments for each physical condition, namely: 1. Test the strength of the standing wide jump muscle 2. Sprint test (30-yard Sprint) 3. Agility test (Illinois agility run) 4. Aerobic endurance test (Bleep Test). Based on the results of physical condition tests on the Pasuruan City Satria Mandiri Team, it shows that the average leg muscle strength test results are 86.23 "very good", speed 4.02 "very good", agility 12.91 "very good", endurance 46.59". The conclusion obtained in the study was that the level of physical ability which included explosive power, speed, agility and aerobic endurance of Satria Mandiri Pasuruan City players showed "Very Good" results which were shown by obtaining a percentage of 89% based on applicable norms.